Contribution of Agricultural Landscape Composition on Shaping the Interaction Between Pests and Natural Enemies in Cacao Agroforestry - Akhmad Rizali; Toto Himawan; Novita Yuniasari; Nely Yuliastanti; Muhamad Ari Bachtiar; Emha Dwi Rifqi Rafid (AGRIVITA, Journal of Agricultural Science, 2022)
Studies of the effects of landscape composition on pests and their natural enemies on agroforestry systems is still limited, whereas the system can maintain biodiversity. This research investigated the impact of agricultural landscape composition on shaping the interaction between pests and natural enemies in cacao agroforestry. The study was conducted in twelve cacao plantations spread across five districts in East Java, Indonesia. A sampling of insects was carried out by observing the intensity of pest attacks and the diversity and abundance of predators. The surrounding landscape of the cacao field was characterized by manually digitalizing the land use. The results found two main pests attacking all cacao plantations: cacao pod borer, Conophomorpha cramerella (CPB) with attack intensity 0.72-12.05%, and Helopeltis sp. with attack intensity 12.39-42.24%. Management of cacao plantations, such as intensification and canopy cover, significantly affected the attack intensity of CPB but not Helopeltis sp. Based on the generalized linear model, the landscape composition, especially the patch number of natural habitats, positively impacted CPB attack intensity and predator abundance. However, predator abundance harmed CPB attack intensity. In conclusion, the proportion of natural habitat in agricultural landscapes contributes to reducing the attack intensity of pests via maintaining natural enemy abundance.